Preaching Biblically in the Nigerian Prosperity Gospel Context - Biwul, Joel K. T. (African Journol of Evangelical Theology, 2013)
The one who lays claim to the pulpit ministry has no other business but that of preaching the Word of God. This article argues that biblical preaching is fast disappearing from the Nigerian pulpit because of wrong motivation. It also argues that this situation has adverse effects on Christians’ spirituality and the Christian witness. It concludes that preachers of a different gospel in Nigeria must make the Scripture central and be willing to submit themselves to adequate and proper training in hermeneutical principles and homiletical rudiments for effective biblical preaching
free